Improvements in Fluvial Stability Associated with Two‐Stage Ditch Construction in Mower County, Minnesota1. (26th June 2017) - Krider, Lori; Magner, Joseph; Hansen, Brad; Wilson, Bruce; Kramer, Geoffrie; Peterson, Joel; Nieber, John
Abstract: Water quality and stream habitat in agricultural watersheds are under greater scrutiny as hydrologic pathways are altered to increase crop production. Agricultural drainage ditches function to remove water quickly from farmed landscapes. Conventional ditch designs lack the form and function of natural stream systems and tend to be unstable and provide inadequate habitat. In October of 2009, 1.89 km of a conventional drainage ditch in Mower County, Minnesota, was converted to an alternative system with a two‐stage channel to investigate the improvements in water quality, stability, and habitat. Longitudinal surveys show a 12‐fold increase in the pool‐riffle formation. Cross‐sectional surveys show an average increase in bankfull width of approximately 10% and may be associated to an increased frequency in large storm events. The average increase in bankfull depth was estimated as 18% but is largely influenced by pool formation. Rosgen Stability Analyses show the channel to be highly stable and the banks at a low risk of erosion. The average bankfull recurrence interval was estimated to be approximately 0.30 years. Overall, the two‐stage ditch design demonstrates an increase in fluvial stability, creating a more consistent sediment budget, and increasing the frequency of important instream habitat features, making this best management practice a viable option for addressing issues of erosion, sediment imbalance, and poor habitat in agricultural drainage systems.